Relationship between overweight at 6 years of age and socioeconomic conditions at birth, breastfeeding, initial feeding practices and birth weight - Cabral Domingos da ROSA, Letícia; TRAEBERT, Eliane; Dias NUNES, Rodrigo; GHIZZO FILHO, João; TRAEBERT, Jefferson (Revista de Nutrição, 2023)
Objective To review the relationship between overweight at 6 years of age and socioeconomic conditions at birth, breastfeeding, early feeding practices and birth weight. Methods A cross-sectional study was carried out involving 473 six-year-old schoolchildren from public and private schools living in a municipality in Southern Brazil. Sociodemographic and breastfeeding data and other initial feeding practices were obtained through interviews with the mothers at home. Birth weight and gestational age were obtained from the child’s health card. Anthropometric data of the schoolchildren were collected during school visits. Bivariate and multivariate analyzes were performed using the Poisson Regression between the independent variables and overweight. Results The prevalence of overweight was 33.2%; 83.2% of the children were breastfed and out of these, 48.4% were breastfed only in the first six months. Non-breastfed children exhibited a 20% higher overweight prevalence (PR=1.20; 95%CI 1.13; 1.28). Children with exclusive breastfeeding for six months exhibited a lower overweight prevalence (PR=0.94; 95%CI 0.89; 0.99). Conclusion In this study, breastfeeding showed to be a protective factor for overweight.